2017
DOI: 10.3389/fneur.2017.00074
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Hematoma Expansion and Perihemorrhagic Edema after Intracerebral Hemorrhage: From Bench Work to Practical Aspects

Abstract: Intracerebral hemorrhages (ICH) represent about 10–15% of all strokes per year in the United States alone. Key variables influencing the long-term outcome after ICH are hematoma size and growth. Although death may occur at the time of the hemorrhage, delayed neurologic deterioration frequently occurs with hematoma growth and neuronal injury of the surrounding tissue. Perihematoma edema has also been implicated as a contributing factor for delayed neurologic deterioration after ICH. Cerebral edema results from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 142 publications
0
64
0
1
Order By: Relevance
“…Delayed perihematomal edema is likely to be a clinical indicator for poor prognosis or a higher MRS score in our study, of which proves to be a problem that clinicians should be highly aware. Prior study in 2016 identified that PHE volume increases with time, and increasing studies founded that PHE is responsible for the prognosis of sICH patients, as well as DHE . Hence, it is quite prerequisite to analyze the possible risk factors that may lead to DHE so that physicians could take better treatment as early as possible in order to reduce the subsequent deterioration and improve patients' functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed perihematomal edema is likely to be a clinical indicator for poor prognosis or a higher MRS score in our study, of which proves to be a problem that clinicians should be highly aware. Prior study in 2016 identified that PHE volume increases with time, and increasing studies founded that PHE is responsible for the prognosis of sICH patients, as well as DHE . Hence, it is quite prerequisite to analyze the possible risk factors that may lead to DHE so that physicians could take better treatment as early as possible in order to reduce the subsequent deterioration and improve patients' functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior study in 2016 identified that PHE volume increases with time, 2 and increasing studies founded that PHE is responsible for the prognosis of sICH patients, 3,13,14 as well as DHE. 15 Hence, it is quite prerequisite to analyze the possible risk factors that may lead to DHE so that physicians could take better treatment as early as possible in order to reduce the subsequent deterioration and improve patients' functional outcomes. Results from our patients in the DHE multifactor analysis study showed that initial hematoma volume and the effects of age are risk factors for DHE after sICH, concluding that the larger the initial hematoma volume, the more prone to DHE, which is in accordance with the results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, neuroimaging is considered mandatory [1]. Hematoma and hemorrhage growth correlates with neurological deterioration and increased morbidity and mortality [79]. Therefore, follow up of intracranial hemorrhage with imaging has become an important element in treatment of brain injuries [10] and is part of the clinical routine [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the acute phase, during the first few days, PHE is sustained by coagulation cascade, thrombin production, immune reaction, and inflammatory cells . Finally, beginning from approximately 72 hours after ICH, PHE formation involves erythrocyte lysis and hemoglobin‐induced toxicity . PHE may contribute to an overall increase in peri‐hematoma volume by 75%, and several studies associated it with an increased risk of poor outcome …”
Section: Primary and Secondary Brain Injury Following Cerebral Hematomamentioning
confidence: 99%
“…Finally, beginning from approximately 72 hours after ICH, PHE formation involves erythrocyte lysis and hemoglobin‐induced toxicity . PHE may contribute to an overall increase in peri‐hematoma volume by 75%, and several studies associated it with an increased risk of poor outcome …”
Section: Primary and Secondary Brain Injury Following Cerebral Hematomamentioning
confidence: 99%